Kinetics and Mechanism of Oxidation of β-Benzoyl Propionic Acids by Pyridinium Chlorochromate in Aqueous Acetic Acid Medium - Sahaya Amutha, P.; Mathiyalagan, N. (Asian Journal of Chemistry, 2010)
The kinetics of the oxidation of six substituted β-benzoyl propionic acids –OC2H5, –CH3, –Cl and –Br) by pyridinium chloro chromate (PCC) in aqueous acetic acid medium is reported here. The reaction rate shows first order dependence on [substrate], [PCC] and [H+]. The rate of the reaction increases with decrease in dielectric constant of the medium. Increase in the ionic strength of the medium has negligible effect on the rate of the reaction. The rates satisfactorily correlate with Hammet's equation and electron releasing substituents accelerate the rate of the reaction. Arrhenius and activation parameters have been calculated by studying the reaction rate at different temperatures (308-323 K). The major product of oxidation of the keto acids (KA) is the corresponding benzoic acid. A most probable mechanism is also proposed.